Factors Influencing Bali Women's Decision to Enter The Labor Market in West Denpasar Sub-District - Padmayanti, Ni Luh Putu; Marhaeni, A.A Istri Ngurah (Journal of Comprehensive Science, 2024)
This study aims to analyze the simultaneously and partially effect of age, reconciliation of gender roles, work ethic of Balinese women, husband's income and education on the decision of Balinese women to enter the labor market in West Denpasar District. Analyze the role of education in moderating effect of husband's income and to find out the variables that have a dominant effect on the decision of Balinese women to enter the job market in West Denpasar District. This research design uses quantitative methods with a total sample of 100 married women. This study uses primary data collected through observation, structured interviews and indepth interviews. Data analysis techniques were carried out by logistic regression analysis, moderation, and dominant test. The results showed that age, gender role reconciliation, Balinese women's work ethic, husband's income and education simultaneously had a significant effect on the chances of Balinese women's deciding to enter the labor market. Partially, age, reconciliation of gender roles, Balinese women's work ethic, and education have a positive and significant effect on the chances of Balinese women's deciding to enter the labor market while, husband's income has no negative or insignificant effect of Balinese women's deciding to enter the labor market. The level of education as a moderating variable weakens the effect of husband's income on the chances of Balinese women's deciding to enter the labor market. Education has a dominant effect on the chances of Balinese women's deciding to enter the labor market.